Modern C : Efficient and Scalable Application Development : Leverage the modern features of C++ to overcome difficulties in various stages of application development /: Efficient and Scalable Application Development : Leverage the modern features of C++ to overcome difficulties in various stages of application development. (2018) - Grimes, Richard; Bancila, Marius
No abstract available